Effects of pseudoparasitism on total hemocyte count and celluar encapsulation of Pieris rapae pupae - CAI Jun; LÜ Hui-ping; YE Gong-yin; HU Cui (浙江大学学报. 农业与生命科学版)
The pseudoparasitism method was used to evaluate physiological activities of some factors from female adults of Pteromalus puparum (Hymenoptera: Pteromalidae). As a small white butterfly, Pieris rapae pupae were pseudo-parasitized by female wasps of Pteromalus puparum exposed to γ-ray irradiation with 150 Gy, it was clear that irradiated wasps could normally parasitize their host pupae and result in the suppression of host hemocyte immune, like normal wasps with non-irradiation. Changes in total hemocyte count and mortality of hemocytes, as well as the spread percentage of plasmatocytes, in host pupae parasitized by irradiated wasps were almost similar to those in host pupae parasitized by normal wasps. However, such changes didn't encounter in punctured host pupae. According to the results mentioned above, it implied that the inhibition of hemocyte immune in parasitized host pupae of the small white butterfly was mainly caused by immunosuppression factors from female adults of Pteromalus puparum.